Hormetic Electric Field Theory of Pattern Formation - Egil Fosslien (SAGE Publishing, 2010)
The hormetic morphogen theory of curvature ( Fosslien 2009 ) proposes that hormetic morphogen concentration gradients modulate the synthesis of adenosine triphosphate (ATP) by cells along the gradients (field cells) and thus regulate their proliferation and induce curvature such as vascular wall curvature; however, it is unclear whether such morphogen gradients can also determine the histological pattern of the walls. Here, I propose that the ATP gradients modulate export of H + by vacuolar H + -ATPase (V-ATPase) located on the surface of field cells and generate extracellular ion concentration gradients, ion currents and electrical fields along the paths of morphogen gradients. In vitro, electrical fields can induce directional migration and elongation of vascular cells and align the cells with their long axis perpendicular to electrical field vectors ( Bai et al. 2004 ). I suggest that likewise, in vivo vascular transmural electrical fields induced by hormetic morphogen concentration gradients can modulate cell shape i.e. cell elongation and cell curvature, and determine cell orientation. Moreover, I suggest that the electrical fields can modulate bidirectional cell migration and cell sorting via dynamic hormetic galvanotaxis analogous to in vitro isoelectric focusing in proton gradients, thus, hormetic morphogen gradients can determine the curvature of vessel walls and their histological patterns.